Stability analysis of Hub dam under rapid drawdown - Salman Mohammed Mohsin; Abraheim Ahmed Kamil; Al-Attabi Ali Mohammed Ali Naji (Open Engineering, 2024)
The purpose of this study was to calculate the Hub dam’s slope stability analysis in a rapid drawdown scenario. Using the slide software, we compared four distinct analytic techniques – the Bishop, Janbu, ordinary way of slicing, and Morgenstern-Price approach – to determine whether or not a given slope would remain stable at the highest possible water level. According to the simulation outcomes, the portion of the dam upstream directly impacts the safety factor. The upstream safety factors, calculated using the Bishop approach, are 2.122 for steady-state seepage and 2.023 for the fast drawdown scenario. This ensures the Hub dam’s stability even under rapid drawdown conditions.